RETRACTED: LacI-Family Transcriptional Regulator DagR Acts as a Repressor of the Agarolytic Pathway Genes in Streptomyces coelicolor A3(2) - Tsevelkhoroloo, Maral; Shim, So Heon; Lee, Chang-Ro; Hong, Soon-Kwang; Hong, Young-Soo (Frontiers in Microbiology, 2021)
Actinobacteria utilize various polysaccharides in the soil as carbon source by degrading them via extracellular hydrolytic enzymes. Agarose, a marine algal polysaccharide composed of D-galactose and 3,6-anhydro-L-galactose (AHG), is one of the carbon sources used by S. coelicolor A3(2). However, little is known about agar hydrolysis in S. coelicolor A3(2), except that the regulation of agar hydrolysis metabolism is strongly inhibited by glucose as in the catabolic pathways of other polysaccharides. In this study, we elucidated the role of DagR in regulating the expression of three agarase genes (dagA, dagB, and dagC) in S. coelicolor A3(2) by developing a dagR-deletion mutant (Δsco3485). We observed that the Δsco3485 mutant had increased mRNA level of the agarolytic pathway genes and 1.3-folds higher agarase production than the wild type strain, indicating that the dagR gene encodes a cluster-suited repressor. Electrophoretic mobility shift assay revealed that DagR bound to the upstream regions of the three agarase genes. DNase 1 footprinting analysis demonstrated that a palindromic sequence present in the upstream region of the three agarase genes was essential for DagR-binding. Uniquely, the DNA-binding activity of DagR was inhibited by AHG, one of the final degradation products of agarose. AHG-induced agarase production was not observed in the Δsco3485 mutant, as opposed to that in the wild type strain. Therefore, DagR acts as a repressor that binds to the promoter region of the agarase genes, inhibits gene expression at the transcriptional level, and is derepressed by AHG. This is the first report on the regulation of gene expression regarding agar metabolism in S. coelicolor A3(2).